Polyoxygenated seco-cyclohexenes and other constituents from Uvaria valderramensis. (April 2017) - Macabeo, Allan Patrick G.; Rubio, Peter Yuosef M.; Higuchi, Tsunehiko; Umezawa, Naoki; Faderl, Christian; Budde, Simon; Bangcaya, Porferio S.; Alejandro, Grecebio Jonathan D.
Abstract: Phytochemical study on the Philippine endemic Annonaceae plant Uvaria valderramensis afforded a new highly oxygenated seco -cyclohexene derivative, valderepoxide (1 ), along with the six known compounds uvamalols D (2 ) and G (3 ), grandiuvarone (4 ), 2′-hydroxy-3′, 4′, 6′-trimethoxychalcone (5 ), valderramenol B (6 ) and benzoic acid. The structure of1 was determined through extensive spectroscopic analyses including 1D, 2D NMR and HRESIMS. Its relative stereochemistry was established using 2D-NOESY. This is the first report on the isolation of polyoxygenated compounds1 –3 and chalcone5 from U. valderramensis . Graphical abstract: Highlights: Seven compounds were isolated and identified from U. valderramensis. A new polyoxygenated seco -cyclohexene derivative, valderepoxide is reported. Co-occurrence of a rare chlorinated oxidized seco -cyclohexene uvamalol D previously isolated from U. macrophylla. Chemotaxonomic relationship between U. valderramensis and other Asian Uvaria species is discussed.